Exit from aid: An analysis of donor experiences - Maria Ana Jalles d'Orey; Annalisa Prizzon (Overseas Development Institute (ODI), 2019)
Over the past 15 years, 35 low-income countries have joined the ranks of the world's middle-income countries. By 2030, a further 29 countries are expected to graduate from the list of countries eligible for official development assistance. These trends reflect the strong and sustained economic growth achieved in most parts of the developing world. Because of this improved income status, several dimensions of the development finance landscape are likely to evolve for most MICs. While income per capita only partly reflects the overall economic and social development of a country, the move to middle-income country status can significantly affect the mix of financing resources available to it and often triggers donor discussion on whether to reduce or even phase out financial assistance. This research report analyses the process of transition and exit from bilateral development cooperation programmes from the perspective of the development partners. A companion paper analyses this policy process from the viewpoint of recipient country governments.
Keywords: 330